Evaluation of two vaccine education interventions to improve pertussis vaccination among pregnant African American women: A randomized controlled trial. Issue 11 (13th March 2017) - Kriss, Jennifer L.; Frew, Paula M.; Cortes, Marielysse; Malik, Fauzia A.; Chamberlain, Allison T.; Seib, Katherine; Flowers, Lisa; Ault, Kevin A.; Howards, Penelope P.; Orenstein, Walter A.; Omer, Saad B.
Abstract: Background: Vaccination coverage with tetanus toxoid, reduced diphtheria toxoid, and acellular pertussis (Tdap) vaccine in pregnancy or immediately postpartum has been low. Limited data exist on rigorously evaluated interventions to increase maternal vaccination, including Tdap. Tailored messaging based on the Elaboration Likelihood Model (ELM) framework has been successful in improving uptake of some public health interventions. We evaluated the effect of two ELM-based vaccine educational interventions on Tdap vaccination among pregnant African American women, a group of women who tend to have lower vaccine uptake compared with other groups. Methods: We conducted a prospective randomized controlled trial to pilot test two interventions – an affective messaging video and a cognitive messaging iBook – among pregnant African American women recruited during routine prenatal care visits. We measured Tdap vaccination during the perinatal period (during pregnancy and immediately postpartum), reasons for non-vaccination, and intention to receive Tdap in the next pregnancy. Results: Among the enrolled women (n = 106), 90% completed follow-up. Tdap vaccination in the perinatal period was 18% in the control group; 50% in the iBook group (Risk Ratio [vs. control group]: 2.83; 95% CI, 1.26–6.37), and 29% in the video group (RR: 1.65; 95% CI, 0.66–4.09). From baseline to follow-up, women's reported intention to receive Tdap during the next pregnancy improved in all three groups. Among unvaccinated women, the most common reason reported for non-vaccination was lack of a recommendation for Tdap by the woman's physician. Conclusions: Education interventions that provide targeted information for pregnant women in an interactive manner may be useful to improve Tdap vaccination during the perinatal period. However, larger studies including multiple racial and ethnic groups are needed to evaluate robustness of our findings. Trial Registration: clinicaltrials.gov Identifier:NCT01740310 .